A review of the communications and multimedia act 1998 in achieving media pluralism / Mazlina Mohamad Mansor @ Mansoor and Zaiton Hamin - Mohamad Mansor @ Mansoor, Mazlina; Hamin, Zaiton (Faculty of Law, 2011)
Achieving media pluralism is at the heart of the public interest policy in a democratic society (Just, 2009). It establishes the tenets of having different independent media owners with the availability of a variety range of contents regardless of patterns of demand (Doyle, 2002). The communications and multimedia law is expected to advance these public policy objectives via the structural regulation (ownership control), behavioral regulation (content control) and/or technical regulation (transmission control). This research argues that Malaysia have taken a light and a relatively passive approach in addressing the issue of media pluralism via the communications and multimedia law. The existence of one Malaysian public listed company, Media Prima Berhad owning majority of the free-to-air commercial television stations nationwide i.e TV3, 8TV, ntv7 and Channel 9, raised the concern of the formation of one gigantic conglomerate controlling majority of the market. This development is not in line with the principle of media pluralism.